Modes of Action of Microbial Biocontrol in the Phyllosphere - Legein, Marie; Smets, Wenke; Vandenheuvel, Dieter; Eilers, Tom; Muyshondt, Babette; Prinsen, Els; Samson, Roeland; Lebeer, Sarah (Frontiers in Microbiology, 2020)
A fast-growing field of research focuses on microbial biocontrol in the phyllosphere. Phyllosphere microorganisms possess a wide range of adaptation and biocontrol factors, which allow them to adapt to the phyllosphere environment and inhibit the growth of microbial pathogens, thus sustaining plant health. These biocontrol factors can be categorized in direct, microbe–microbe, and indirect, host–microbe, interactions. This review gives an overview of the modes of action of microbial adaptation and biocontrol in the phyllosphere, the genetic basis of the mechanisms, and examples of experiments that can detect these mechanisms in laboratory and field experiments. Detailed insights in such mechanisms are key for the rational design of novel microbial biocontrol strategies and increase crop protection and production. Such novel biocontrol strategies are much needed, as ensuring sufficient and consistent food production for a growing world population, while protecting our environment, is one of the biggest challenges of our time.